ANALISIS PERILAKU KONSUMEN DALAM MENGONSUMSI BUAH DAN PRODUK OLAHANNYA DIMASA PANDEMI COVID-19: PERILAKU KONSUMEN DALAM MENGONSUMSI BUAH DAN PRODUK OLAHANNYA DIMASA PANDEMI COVID-19 - Rahmawati Setiyani; Retna Dewi Lestari; Aldira Dwi Saputri (Innofarm:Jurnal Inovasi Pertanian, 2023)
The COVID-19 pandemic is one of the toughest periods for all countries, including Indonesia. One way to increase the body's immunity can be done through the consumption of healthy foods, namely fruits and their processed products. The aim of the research is to analyze consumer behavior in the city of Surakarta in consuming fruit and its processed products. The stages in the research are (1) determining the respondents, (2) identifying factors that influence consumer decisions, (3) collecting and analyzing data. Respondents in the study were 100 respondents, who are in the adult age group, namely ages 20 to 60 years who live in the city of Surakarta and have consumed fruit and processed products. Spearman's Rank correlation test was used for data analysis in order to know the relationship between knowledge variables and situational variables with consumer decisions in consuming fruit and processed products. Based on the data analysis, the P value <0.05, so it can be concluded that knowledge variables and situational variables have a significant and direct relationship with consumer behavior in consuming fruit and processed products.